2018
DOI: 10.1016/j.immuni.2018.11.018
|View full text |Cite
|
Sign up to set email alerts
|

Commensals Suppress Intestinal Epithelial Cell Retinoic Acid Synthesis to Regulate Interleukin-22 Activity and Prevent Microbial Dysbiosis

Abstract: Summary Retinoic acid (RA), a vitamin A metabolite, regulates transcriptional programs that drive protective or pathogenic immune responses in the intestine, in a manner dependent on RA concentration. Vitamin A is obtained from diet and is metabolized by intestinal epithelial cells (IECs), which operate in intimate association with microbes and immune cells. Here we found that commensal bacteria belonging to class Clostridia modulate RA concentration in the gut by suppressing the expression of retinol dehydrog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
120
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(125 citation statements)
references
References 74 publications
3
120
1
1
Order By: Relevance
“…Interestingly, microbiota is directly regulating the availability of RA . Specifically, Clostridia species influence epithelial RA synthesis . A similar population of RORyt + ILC3s is required to induce cryptopatches and intestinal lymphoid follicles (ILFs) after birth .…”
Section: Ilc Development and Microbiota In Prenatal And Early Lifementioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, microbiota is directly regulating the availability of RA . Specifically, Clostridia species influence epithelial RA synthesis . A similar population of RORyt + ILC3s is required to induce cryptopatches and intestinal lymphoid follicles (ILFs) after birth .…”
Section: Ilc Development and Microbiota In Prenatal And Early Lifementioning
confidence: 99%
“…IFN‐y is key to fight the infection, and its expression has been reported to be shared by conventional NK cells as well as ILC3s during Salmonella infection in mice with T‐bet + CCR6 − RORγt + ILC3s being the strongest IFN‐y producers . In addition, intestinal IL‐22 expression triggered by intestinal epithelial cell‐derived RA affects antimicrobial peptide expression and bacterial load in S. typhimurium infection …”
Section: Microbiota – Ilc Axis During Infectious Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, IL-22 can promote colonization by other pathogens such as S. typhimurium by controlling growth of its niche competitor E. coli [112]. In a study by Grizotte-Lake et al [113] they found that commensal microbes suppress small intestinal epithelial expression of Rdh7, an enzyme required for retinoic acid (RA) production, resulting in reduced RA in SPF mice compared to germ-free mice. This effect was due to sporeforming Clostridia sp.…”
Section: Metabolic Interplay Between Host Microbiota and Pathogensmentioning
confidence: 99%
“…Similarly, maternal retinoic acid (RA) induces fetal type 3 innate lymphoid cells and therefore secondary lymphoid organ development [91]. in the gut can modulate RA concentration by suppressing the expression of retinol dehydrogenase 7 (Rdh7) in intestinal epithelial cells [92]. in the gut can modulate RA concentration by suppressing the expression of retinol dehydrogenase 7 (Rdh7) in intestinal epithelial cells [92].…”
Section: Igg Mediates Bacterial Transfer In Uteromentioning
confidence: 99%